Experimental pain processing in individuals with cognitive impairment: current state of the science. Issue 8 (August 2015) - Defrin, Ruth; Amanzio, Martina; de Tommaso, Marina; Dimova, Violeta; Filipovic, Sasa; Finn, David P.; Gimenez-Llort, Lydia; Invitto, Sara; Jensen-Dahm, Christina; Lautenbacher, Stefan; Oosterman, Joukje M.; Petrini, Laura; et al.
Abstract : Abstract: Cognitive impairment (CI) can develop during the course of ageing and is a feature of many neurological and neurodegenerative diseases. Many individuals with CI have substantial, sustained, and complex health care needs, which frequently include pain. However, individuals with CI can have difficulty communicating the features of their pain to others, which in turn presents a significant challenge for effective diagnosis and treatment of their pain. Herein, we review the literature on responsivity of individuals with CI to experimental pain stimuli. We discuss pain responding across a large number of neurological and neurodegenerative disorders in which CI is typically present. Overall, the existing data suggest that pain processing is altered in most individuals with CI compared with cognitively intact matched controls. The precise nature of these alterations varies with the type of CI (or associated clinical condition) and may also depend on the type of pain stimulation used and the type of pain responses assessed. Nevertheless, it is clear that regardless of the etiology of CI, patients do feel noxious stimuli, with more evidence for hypersensitivity than hyposensitivity to these stimuli compared with cognitively unimpaired individuals. Our current understanding of the neurobiological mechanisms underpinning these alterations is limited but may be enhanced through the use of animal models of CI, which also exhibit alterations in nociceptive responding. Further research using additional behavioural indices of pain is warranted. Increased understanding of altered experimental pain processing in CI will facilitate the development of improved diagnostic and therapeutic approaches for pain in individuals with CI.